Little House in the Mountains? A small Mesolithic structure from the Cairngorm Mountains, Scotland. (April 2018) - Warren, Graeme; Fraser, Shannon; Clarke, Ann; Driscoll, Killian; Mitchell, Wishart; Noble, Gordon; Paterson, Danny; Schulting, Rick; Tipping, Richard; Verbaas, Annemieke; Wilson, Clare; Wickham-Jones, Caroline
Abstract: This paper describes a small Mesolithic structure from the Cairngorm Mountains, Scotland. Excavations at Caochanan Ruadha identified a small oval structure (c. 3 m × 2.2 m) with a central fire setting, in an upland valley (c.540 m asl). The site was occupied at c. 8200 cal BP and demonstrates hunter-gatherer use of the uplands during a period of significant climatic deterioration. The interpretation of the structure is primarily based on the distribution of the lithic assemblage, as the heavily podsolised soils have left no trace of light structural features. The lithic assemblage is specialised, dominated by microlith fragments, and functional analysis has identified different uses of different areas inside the structure. The identification of small, specialised Mesolithic sites is unusual and this paper will discuss the evidence for the presence of the structure and its use, compare it to other Mesolithic structures in Britain and highlight some methodological implications. Highlights: Presents evidence for small Mesolithic structure found in upland environment at c 540 mOD Site occupied c 8200 cal BP Short term occupation, very specialised lithic assemblage Possible evidence for different activity areas in interior